Development of Electronic Services at Industrial Enterprises in the Digital Economy - Muratovich, Abduraimov Bun’et (International Journal on Economics, Finance and Sustainable Development (IJEFSD), 2023)
The article examines the pace of development of electronic services at industrial enterprises in the context of the development of the digital economy in Uzbekistan and the factors affecting it.